Faktor Risiko Diabetes Mellitus di Puskesmas Mangasa Kota Makassar - Junaidi; Hasani, Ruslan; Jalil, Nuraeni; Dilla, Ramlah (STIKes Panti Rapih, 2021)
Background: Diabetes mellitus is a chronic disease that is suffered by the sufferer for life. Causes are genetic, lifestyle, BMI, stress management and physical activity / xercise. Objective: The purpose of this study was to determine the risk factors for the incidence of DM. at the Puskesmas Mangasa, Makassar City. Methods: This research method is descriptive analytic with a case control study design. Place of research at Puskesmas Mangasa. The research was carried out on 1- 21 September 2020. Sampling used purposive sampling. The sample size of the study was 47 samples. Results: The results showed diet value OR = 5.111 (95% CI: 1.36-19.16), p = 0.028, BMI OR value = 0.242 (95% CI: 0.064-0.906), p = 0.065, Stress Management OR Value = 0.609 (95% CI: 0.149-2.484), p = 0.496 and sports activities OR = 0.267 (95% CI: 0.071-1.007), p = 0.090. Conclusion: The conclusion of this study is that there is a relationship between diet and the incidence of DM, there is no relationship between BMI and the incidence of DM, there is no relationship between stress management and the incidence of DM and there is no relationship between sports activities and the incidence of DM.